Is pneumonectomy justifiable for patients with a locoregional recurrence or persistent disease after curative intent chemoradiotherapy for locally advanced non-small cell lung cancer?. (December 2020) - Joosten, Pieter J.M.; Dickhoff, Chris; van der Noort, Vincent; Klomp, Houke M.; van Diessen, Judi N.A.; Dahele, Max; Bahce, Idris; Veenhof, Alexander A.F.A.; Smit, Egbert F.; Hartemink, Koen J.
Highlights: Salvage surgery for local recurrence should be considered in selected patients. Salvage pneumonectomy is associated with minimal morbidity and mortality. DFS and OS are better in patients in whom an R0 resection was performed. Recurrence and subsequent surgery more than 12 months after CRT seem to do better. Abstract: Objectives: Locoregional recurrence and persistent/progressive disease after curative-intent definitive chemoradiotherapy (CRT) for non-small cell lung cancer (NSCLC) is challenging to manage, as salvage options are limited. Selected patients might be candidates for resection. This study evaluated the outcomes of patients after salvage surgery for locoregional recurrence, focusing specifically on morbidity and mortality after salvage pneumonectomy. Materials and Methods: This retrospective study included patients from 2 tertiary referral hospitals who underwent salvage pulmonary resection for locoregional recurrence or disease persistence/progression >12 weeks after completion of curative intent high dose (>60 Gy) CRT. Disease-free (DFS) and overall survival (OS) were estimated and the influence of patient and treatment characteristics on these endpoints was assessed. Results: A total of 30 patients treated between 2015–2017 were identified with a median age of 60 years (range 42–72 years), 67 % were male. Median follow-up was 47 months (95 % CI 46-NR). Pneumonectomy was performed in 13/30 (43 %) patients and lobectomy in 17/30 (57 %). Median DFS and OS after pneumonectomy/lobectomy were 14/6 and NR/17 months, respectively. 30 and 90-day mortality for pneumonectomy/lobectomy were 0/12 % and 0/24 % respectively. More favorable survival was seen after pathologically radical resection, i.e. R0, and when surgery was performed more than 12 months after completion of CRT. Conclusion: Salvage surgery, including pneumonectomy is associated with acceptable outcomes in selected patients with recurrent or persistent/progressive NSCLC after curative-intent high dose CRT. Patients should be assessed for the probability of an R0 resection, and patients with a locoregional recurrence more than 12 months after treatment with CRT may benefit most from salvage surgery.